Correlation of Hepatocyte Growth Factor Levels with Myopia Degree and Axial Length in Outpatient Myopic Adolescents - Aldy, Fithria; Yanni, Gema Nazri; Siregar, Jelita (Faculty of Medicine, Universitas Padjadjaran, 2024)
Myopia is the most common ophthalmic condition worldwide, with an estimated 22.9% of the population or 1.406 billion people affected. Studies of candidate gene-associated refraction abnormalities have also identified several genes that cause vulnerability myopia, including the hepatocyte growth factor (HGF) and hepatocyte growth factor receptor (MET) genes. The purpose of the study was to analyze the correlation between hepatocyte growth factor (HGF) levels, degrees of myopia, and long axial in adolescents with myopia treated as outpatients in Universitas Sumatera Utara Hospital. This study applied the cross-sectional analytical approach. The inclusion criterion for the participants was patients diagnosed as suffering from myopia by the Ophthalmology Outpatient Clinic of the Universitas Sumatera Utara Hospital. Sampling was performed consecutively with a minimum sample size of 25 patients in control group and 25 patients in the case group. This study revealed that the mean axial length of the right eye in the case group was 23.82 mm, with a significant difference in the axial length between the case and control groups. The mean HGF level in the myopia group was 510.49 ng/mL, which was not significantly different from the mean HGF level in the control or emmetropic group. The HGF levels were highest in the group of subjects with moderate myopia, with an average of 551.87 ng/mL, and differences in HGF levels were identified in different degrees of myopia. Thus, no significant correlation is identified between the HGF levels, axial length, and myopia degree.